2014
DOI: 10.3906/vet-1401-97
|View full text |Cite
|
Sign up to set email alerts
|

Screening for S32G mutation of BMP15 gene in 18 goat breeds

Abstract: doi:10.3906/vet-1401-9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…They suggested that BMP15 gene may be a major gene which affects the prolificacy in Funiu white goats. Feng et al (40) identified one mutation (A898 G) in BMP15 gene in Chinese goats and the allele G was found to be associated with high litter size in Jining Grey goats and Matou goats. This mutation is a nonsynonymous mutation which changes serine to glycine in the putative protein.…”
Section: Resultsmentioning
confidence: 98%
“…They suggested that BMP15 gene may be a major gene which affects the prolificacy in Funiu white goats. Feng et al (40) identified one mutation (A898 G) in BMP15 gene in Chinese goats and the allele G was found to be associated with high litter size in Jining Grey goats and Matou goats. This mutation is a nonsynonymous mutation which changes serine to glycine in the putative protein.…”
Section: Resultsmentioning
confidence: 98%
“…To define the source of heterogeneity, we performed a sensitivity analysis by removing studies one by one. The results indicated that studies performed by Dong and Du (2010) on the Lubei White breed and by Feng et al (2014) and Moghadaszadeh et al (2015) influenced overall results of the meta-analysis by increasing the P value under an additive genetic model. One possible reason for this could be that studies with a larger Z value have SMD farther from overall SMD, which can lead to the increased P value.…”
Section: Discussionmentioning
confidence: 89%
“…On the contrary, sensitivity analysis showed significant difference in litter size by dropping studies performed by Dong and Du (2010) on the Lubei White breed and by Feng et al (2014) andMoghadaszadeh et al (2015) under the additive model (Table 8 and Fig. 3).…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 87%
See 1 more Smart Citation
“…Theses base changes resulting in substitutions of amino acids that might be a major mechanism that caused the differential prolificacy of mentioned goat breeds. In Chinese goats, Feng et al (2014) detected by using PCR-RFLP one mutation, A898G in BMP15 gene. The results indicated that the allele G associated with high litter size in two strains of such goats, Jining Grey and Matou goats.…”
Section: Pcr-sscp Of Fecx I Of Bmp15 Genementioning
confidence: 99%